Philodryas patagoniensis bite and local envenoming Picada por Philodryas patagoniensis e envenenamento local - Sérgio de Andrade Nishioka; Paulo Vitor Portella Silveira (Revista do Instituto de Medicina Tropical de São Paulo, 1994)
A 5-year-old boy bitten by a specimen of Philodryas patagoniensis, a colubrid snake currently classified as nonvenomous, developed signs of local envenoming characterized by swelling and warmth on the bitten limb. This is the first time that local envenoming following Philodryas patagoniensis bite is recognized. Based on the clinical findings and misidentification of the snake, the patient was treated as a victim of Bothrops bite, having received unnecessarily the specific antivenom. Educational efforts to make doctors and health workers capable to identify correctly venomous snakes are necessary, to avoid inappropriate indication of antivenom and decrease the risk of its potentially harmful untoward effects. Examination of the bite site can be useful to the differential diagnosis between pit viper and colubrid bites. Um menino de 5 anos de idade foi picado por um espécime de Philodryas patagomensis, uma serpente colubrídea tida como não peçonhenta, tendo apresentado sinais de envenenamento local caracterizados por edema e calor. Esta é a primeira vez que se descreve que Philodryas patagoniensis pode causar envenenamento local. Com base nos achados clínicos e na identificação errônea da serpente, o paciente foi tratado como vítima de acidente botrópico, tendo recebido antiveneno específico. São necessários esforços para proporcionar a médicos e outros profissionais da área de saúde informações para o reconhecimento de serpentes peçonhentas, o que evitaria o uso inapropriado de antiveneno e seus potenciais efeitos adversos. Exame do local da picada pode ser útil para o diagnóstico diferencial entre serpentes da subfamilia Crotalinae (peçonhentas) e da familia Colubridae.